The Effect of Implementing An Integrated Taxpayer Database System For Bpprd Pemko Medan and Digitizing Local Tax Reporting Services (E-Tax) in Increasing Optimization of Regional Tax Revenue (Survey of Restaurants in City Medan) - Nurlinda Nurlinda; Rini Indahwati; Tulus Pardamean Sipahutar (Jurnal Syntax Transformation, 2022)
Tax modernization is an improvement of the tax system as a whole including improving regulations, improving administration and increasing the tax base. Optimization of the potential that exists in the region is needed to be able to improve people's welfare. Based on this phenomenon, the study observed how the integration of the database system and digitization of the taxation system was able to optimize regional tax revenues for Pemko Medan. This research is a quantitative research. The side technique uses purposive sampling of 30 samples. The research data source is primary data, data collection techniques using questionnaires and data analysis techniques using descriptive statistics. The results of this study indicate that tax modernization has an effect on optimizing regional tax revenues in Medan City. This is in line with the use of an integrated system with government efforts to increase regional tax revenues.